Technological properties of milk gels produced by chymosin and wild cardoon rennet optimized by response surface methodology. (15th December 2017) - Ben Amira, Amal; Mokni, Abir; Yaich, Hela; Chaabouni, Moncef; Besbes, Souhail; Blecker, Christophe; Attia, Hamadi
Highlights: Extraction conditions of wild cardoon rennet were optimized. The applicability of the optimized extract in milk gelation was investigated. Rheological properties and water holding capacity of milk gels were evaluated. Firmness of milk gels produced by chymosin and the optimized extract were similar. Wild cardoon rennet can be employed as an efficient milk-clotting agent. Abstract: The aim of this paper was to optimize extraction conditions of C. cardunculus rennet by response surface methodology, in order to maximize its milk-clotting activity (MCA). The second objective was to examine the effect of different amounts of the optimized extract and the type of milk, on technological characteristics of the obtained gels. Results of the central composite design showed that the optimum extraction conditions, corresponding to maximum MCA (9.550 CAU/mL), were selected as follows: Grinding time 30 s, pH 3, extraction time 50 min and solid to liquid ratio 15 g/100 mL. According to technological properties, it can be concluded that C. cardunculus extract exhibited an excellent efficiency on raw milk, in term of dynamic moduli and gel firmness, as compared to chymosin. A good gelation time and WHC were also obtained. Consequently, the optimized C. cardunculus rennet has the potential to be employed as an efficient milk-clotting agent.